Growing Old in Utopia: From Age to Otherness in American Literary Utopias - Brand, Mark R. (Age, Culture, Humanities: An Interdisciplinary Journal, 2018)
Utopian Studies and Age Studies, as disciplines, have traditionally had little to do with one another despite a great deal of shared scholarly “territory.” This essay examines one such nexus of shared territory: the changing representa-tion of age as a component of social formation in American utopian fictions of the late-nineteenth and early-twentieth centuries. A perceptible shift in Anglophone utopian depictions of aging can be identified in the approximate years 1890-1914, before which aging was largely figured as a non-othering, normative characteristic, and after which aging became a particularlizing and potentially othering feature of identity. Using a “stage” vs. “state” theoretical approach modeled on the work of Andrea Charise, the analysis here focuses on the brief interim where narrative figurations of age became noticeably unstable in utopian literature, fluctuating between othering and non-othering configurations (sometimes both simultaneously) in well-known American utopias such as Ignatius Donnelly’s Caesar’s Column (1890), Jack London’s The Scarlet Plague (1912), and Charlotte Perkins Gilman’s Herland (1915).